Strategy Analysis of the Marketing Mix in the New Normal Era on Orange Picking Tourism in Mojokerto - Tiara Niken Pramesti; Nur Hidayati; M. Ridwan Basalamah (Budapest International Research and Critics University, 2021)
This study aimed to describe the marketing mix strategy in the new normal era on orange picking tourism in Mojokerto. This research was conducted at the orange picking tourist attraction in Klegen Hamlet, Talok Village, Dlanggu District, Mojokerto Regency, East Java Province. This study uses a qualitative approach. Data collection techniques used are interviews, observation, and documentation. The informants of this research are the owners and employees of the orange picking tour in Mojokerto. The study results concluded that there are several marketing strategies in the new normal era applied by the orange picking tourist attraction, namely attracting tourist visitors by free admission for tourists and packing a tour entitled Immunity Tourism.